A Voyage for Regulating Commercial Surrogacy in India: An Analysis of Surrogacy (Regulation) Bill, 2016 - Shekhar, Bandna; K. Dixit, Anil (International Journal of Engineering and Technology, 2019)
To beget a child is a priceless feeling. But for those persons who cannot have their own child, it can be problematice and painful. Surrogacy has emerged as a solution towards this type of situation. India became the top most place for surrogacy after baby M case and it was totally unregulated process.Â There were no rigths for the surrogate mother and child. As different countries around the world having different laws so, there came a situation of conflict of laws. After so many bills finaly Indian Government proposed a novel legislative proposal of Surrogacy Bill 2016, which has put some restrictions for particular individuals who are totally banned and cannot avail the surrogacy process. This bill has put a full stop on commercial surogacy in India. But some critiques says that it is a very haste decision of the government.The present paper has discussed the journey of unregulated surrogacy process towards itsÂ regulation. But whether this has proved fruitful or futile? it is still a matter of dicussion.Â Â